Fostering interests for teaching: job satisfaction and motivation factors of Malaysian TVET instructors - Omar, Muhd Khaizer; Mat Rashid @ Mat Idris, Abdullah; Mohd Puad, Mohd Hazwan; Nor Azman, Ady Hameme (Science Publishing Corporation, 2018)
Often, when the public is asked of what teachers normally do in class, the most common response would be: What else will they do? Teaching students is their core business. In general, the role of teachers in school is restricted to the traditional conception of what teachers should teach. Undoubtedly, the notion of ‘to only teach’ was relevant in the last thirty years unlike now. With respect to this matter, this study explored the reasons why some teachers retain while some leave this noble profession based on previous studies. Also, Adam’s Equity Theory (AET) of motivation was examined. Essentially, the theory served as a guideline for the researchers to ascertain the job satisfaction factors that contributed to the narratives of TVET instructors with regards to their reasoning process. Notably, the research was carried out using a mixed-method design which employs a convergent parallel design. For the purpose of this article, the results were derived from the narrative section through an online survey named Qualtrics. The population of this survey comprised of Malaysian training instructors at the Technical and Vocational Education and Training (TVET) educational institutions. In addition, a thematic analysis using the Atlas.ti software was employed to determine the reasons of TVET instructors retaining in the teaching profession and to identify the contributing factors of job satisfaction. Based on the findings, six themes with regards to teaching job satisfaction factors of TVET instructors were identified: conducive working environment, deep interest towards teaching profession, performing tasks well, satisfactory achievement among students, student factor, and students’ understanding during class. Ultimately, the understanding of teaching job satisfaction among TVET instructors can be construed as an eye-opener to enhance teaching motivation in alignment with the overarching advancement of this field.